Clinical features of patients with cancer of thoracic esophagus and results of their surgical treatment - Jamalov, Fariz; Agayev, Rauf; Akhundov, Idris; Jamalova, Tarana; Huseynov, Shahin; Lyatifova, Lale (Gaceta Médica de Caracas, 2023)
Esophageal cancer takes one of the first places in the structure of morbidity and mortality among malignant diseases. The development of anesthesiology and thoracic resuscitation provided the evolution of the surgical method. Resections of the esophagus with locally-disseminated and complicated forms of cancer have become possible. But even today, the long-term results of surgical treatment don’t satisfy clinicians. Often this is due to the dissemination of the tumor process in most patients at the time of treatment. For this purpose, an analysis of clinical material was carried out, including 89 patients with cancer of thoracic part of esophagus, who underwent reconstructive surgeries (extirpation of the thoracic part of esophagus with simultaneous retromediastinal plasty by stomach tube) in the surgical unit of Republican Clinical Hospital (RCH), n.a. academic M.A.Mir-Gasimov, Baku city. Interventions on the esophagus were performed either of two approaches – upper median laparotomy and left-sided cervicotomy (76 patients – 85,4%) or from three-with the addition of a right sided lateral thoracotomy in the fifth intercostal space (13 patients – 14,6%). There were no deaths due to surgical complications. The fundamental possibility and reasonableness of performing expanded radical interventions has been detected, taking into account the technical resectability of the tumor, which is especially important in working with a group of patients with “late” esophageal cancer criteria, such as the age of the patient, the size of the primary tumors, its local dissemination are not a contraindication to radical surgery.